ON SOME MORE q-SERIES IDENTITIES - Singh, S.N.; Singh, Satya Prakash (Italian Journal of Pure and Applied Mathematics, 2015)
In this paper we have discussed and also generalized some interesting identities found in the 'Lost' notebook of Ramanujan.